2020
DOI: 10.4081/jphr.2020.1852
|View full text |Cite
|
Sign up to set email alerts
|

Undocumented Migrants during the Covid-19 Pandemic: Socio-Economic Determinants, Clinical Features and Pharmacological Treatment

Abstract: Population groups such as undocumented migrants have been almost completely forgotten during the COVID-19 pandemic, though they have been living in all European countries for decades and new arrivals have continued throughout the pandemic. The aim of this study was to investigate their health conditions during the current pandemic. We analysed the records of 272 patients with respiratory issues attending the outpatient clinic of a large charity in Milan, Italy: amongst them, 18 had COVID-19 confirmed by rhino-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Reported difficulties in accessing information and complying with measures are colored by the challenging living and working conditions of UDMs. The UDMs' precarious circumstances are well-known from previous studies in the Netherlands and elsewhere (Schoevers et al, 2009(Schoevers et al, , 2010Woodward et al, 2014) and have been observed in the few other studies on the impact of COVID-19 on UDMs elsewhere (Schoevers et al, 2009;Burton-Jeangros et al, 2020;Devillanova et al, 2020;Fiorini et al, 2020;Mia and Griffiths, 2020;Varga, 2020). In turn, non-compliance poses a health risk as access to healthcare is hampered for UDMs, especially for those who are not aligned with NGO or migrant organizations (Schoevers et al, 2010).…”
Section: Comparison With Literaturementioning
confidence: 80%
See 3 more Smart Citations
“…Reported difficulties in accessing information and complying with measures are colored by the challenging living and working conditions of UDMs. The UDMs' precarious circumstances are well-known from previous studies in the Netherlands and elsewhere (Schoevers et al, 2009(Schoevers et al, , 2010Woodward et al, 2014) and have been observed in the few other studies on the impact of COVID-19 on UDMs elsewhere (Schoevers et al, 2009;Burton-Jeangros et al, 2020;Devillanova et al, 2020;Fiorini et al, 2020;Mia and Griffiths, 2020;Varga, 2020). In turn, non-compliance poses a health risk as access to healthcare is hampered for UDMs, especially for those who are not aligned with NGO or migrant organizations (Schoevers et al, 2010).…”
Section: Comparison With Literaturementioning
confidence: 80%
“…Having to rely on the informal market makes the UDMs subject to low wages, crowded housing, and general exploitation (Parrennas et al, 2018;Varga, 2020), as well as elevated physical and psychological stress (Schoevers et al, 2009;Teunissen et al, 2014a,b;Andersson et al, 2018). This increases their risk for COVID-19 exposure (Burton-Jeangros et al, 2020;Devillanova et al, 2020;Mia and Griffiths, 2020) and severe disease (Fiorini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inequalities and vulnerabilities shown in this study may have been further amplified by the COVID-19 pandemic, which was not captured in our study but should be briefly discussed. Even though healthcare services face an unprecedented demand, groups such as undocumented migrants and migrant women are still facing barriers to access appropriate quality care that contributes to poorer health outcomes [41,42]. Moreover, epidemiological data shows that COVID-19 disproportionately affects patients who have chronic conditions and underlying comorbidities [43].…”
Section: Discussionmentioning
confidence: 99%